2018
DOI: 10.1038/s41388-017-0110-2
|View full text |Cite
|
Sign up to set email alerts
|

Piperlongumine and p53-reactivator APR-246 selectively induce cell death in HNSCC by targeting GSTP1

Abstract: TP53 mutations frequently occur in head and neck squamous cell carcinoma (HNSCC) patients without human papillomavirus infection. The recurrence rate for these patients is distinctly high. It has been actively explored to identify agents that target TP53 mutations and restore wild-type (WT) TP53 activities in HNSCC. PRIMA-1 (p53-Reactivation and Induction of Massive Apoptosis-1) and its methylated analogue PRIMA-1Met (also called APR-246) were found to be able to reestablish the DNA-binding activity of p53 mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 54 publications
3
26
0
Order By: Relevance
“…Although ROS facilitates the progression of cancer to some extent, the accumulation of ROS reaches a threshold and then causes cell death [ 23 ]. Therefore, increasing the ROS level to induce cancer cell death is a well-known anticancer strategy [ 38 40 ]. Evidence shows that pharmaceutical compounds extracted from plants, such as resveratrol, levistolide A and piperlongumine, induce apoptosis through DNA toxicity by the induction of intracellular ROS [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ROS facilitates the progression of cancer to some extent, the accumulation of ROS reaches a threshold and then causes cell death [ 23 ]. Therefore, increasing the ROS level to induce cancer cell death is a well-known anticancer strategy [ 38 40 ]. Evidence shows that pharmaceutical compounds extracted from plants, such as resveratrol, levistolide A and piperlongumine, induce apoptosis through DNA toxicity by the induction of intracellular ROS [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, increasing the ROS level to induce cancer cell death is a well-known anticancer strategy [ 38 40 ]. Evidence shows that pharmaceutical compounds extracted from plants, such as resveratrol, levistolide A and piperlongumine, induce apoptosis through DNA toxicity by the induction of intracellular ROS [ 40 42 ]. In this study, we measured the level of intracellular ROS in melanoma after VB1 treatment, and the results showed that VB1 significantly increases ROS levels, which indicates that the cells were under high oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Piplartine (piperlongumine) is a plant-derived compound found in some Piper species that became a novel potential antineoplastic agent. Potent cytotoxicity, genotoxicity, antitumor, antiangiogenic and antimetastatic properties, in addition to presenting adequate bioavailability and safety profile have been attributed for this molecule and its derivatives [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] . Although its cytotoxic properties have been known for over three decades, the great interest in this molecule has arisen after its cytotoxicity and ability to induce the production of reactive oxygen species (ROS) selectively in cancer cells were described [11] , [12] .…”
Section: Introductionmentioning
confidence: 99%
“…The cysteine-binding PRIMA-1 and APR-246 induce apoptosis through caspase activation [ 75 ]. The efficacy of PRIMA-1 and APR-246 has been demonstrated in many studies investigating various malignancies, but only a few studies have practiced them on OSCC/HNSCC treatment so far [ 76 , 77 ]. Although the studies have confirmed the p53 restoring ability of PRIMA-1 and APR-246, experimental outcomes suggest that their anti-cancer characteristics might be independent of p53 restoration [ 78 ].…”
Section: Targeted Gene Therapymentioning
confidence: 99%